Modern and Classic Wound Dressing Comparison in Wound Healing, Comfort and Cost - Ferdiansyah Mahyudin; Mouli Edward; M Hardian Basuki; Yunus Basrewan; Ansari Rahman (Jurnal Ners, 2020)
Introduction: Wound care has also developed rapidly after the dissemination of the concept of TIME (Tissue, Infection, Moisture, and Wound Edge) in modern dressing (MD). The aim of this study was to compare modern dressings (MDs) and classic dressings (CDs) in terms of patient comfort, cost effectiveness and wound healing.Methods: A prospective study design with total of 25 participants. The sampling technique used was consecutive sampling. Patient comfort was assessed through the frequency of wound care and pain scale using the Visual Analogue Scale (VAS). Cost-effectiveness was assessed using direct and indirect costs. Wound healing was assessed using the Bates-Jensen Wound Assessment Tool (BWAT) score. The data was analyzed using the independent t and Mann-Whitney tests.Results: In terms of comfort, the mean for the number of times that wound care was performed and the pain scale in the participants using MD was (3.07 ± 0.88 times and VAS 4.59  ± 0.72, respectively), which is less compared to using CD (4.60  ±  1.84 times each and VAS 5.43  ± 0.75). Referring to the indirect and direct costs, MD (13.67  ± 6.09 and 527.63  ± 84.47, respectively) has the same cost-effectiveness as CD (14.00  ± 7.64 and 482.68 ± 98.08, respectively). In terms of healing, the mean of the BWAT score in MD (31.26  ± 1.69) was better compared to CD (33.07  ± 1.65).Conclusion: The application of MD has the same cost-effectiveness as CD with a more satisfactory outcome for the wounds in terms of comfort and healing.